The handbook of global communication and media ethics - Fortner, Robert S.; Fackler, Mark. (Chichester, West Sussex, U.K. Wiley-Blackwell, 2011)
"This groundbreaking collection provides a comprehensive picture of the ethical dimensions of communication in a global setting. Bringing together scholars from around the world, this substantial work examines ethical issues raised by globalization, the practice of journalism, popular culture, and media activities, and provides the most detailed and diverse set of essays ever assembled on this vital topic. The editors, along with a team of international communication and media scholars, provides an authoritative overview of the philosophical and theoretical issues associated with global communication and media ethics, including examinations of feminism, ideology, social responsibility, reporting, metanarratives, blasphemy, development, and glocalism, among many others. In addition, the handbook includes international case studies addressing topics such as reporting, censorship, responsibility, terrorism, disenfranchisement, and guilt. The work includes contributions by several Islamic scholars discussing various facets of that religion's engagement with the public sphere, as well as essays dealing with the religious and cultural factors that complicate efforts to understand our world. Fortner and Fackler's innovative collection is both theoretical and practical, and will raise the ethical bar for both scholars and practitioners in the world of global communication and media"--Provided by publisher.
v. II Voiceless glasnost : responding to government pressures and lack of a free press tradition in Russia Problems of application Media use and abuse in Ethiopia Collective guilt as a response to evil : a case of arabs and muslims in the western media Journalists as witnesses to violence and suffering Reporting on religious authority complicit with atrocity The ethics of representation and the internet Authors, authority, ownership and ethics in digital media and news Ethical implications of blogging Journalism ethics in a digital network Now look what you made me do : violence and media accountability Protecting children from harmful influences of media through formal and nonformal media education Ethics and international propaganda Modernization and its discontents : ethics, development and the diffusion of innovations Communication technologies in the arsenal of al Qaeda and Taliban : why the west is not winning the war on terror The ethics of a very public sphere : differential soundscapes and the discourse of the streets Ancient roots and contemporary challenges : Asian journalists try to find the balance Ethics of survival : media, Palestinians, and Israelis in conflict Understanding Bollywood Disenfranchised and disempowered : how the globalized media treat their audiences --a case of India Media and post-election violence in Kenya Questioning journalism ethics in the global age : how Japanese news media report and support immigrant law revision Peace communication in Sudan : toward infusing a new Islamic perspective Anita Dighe -- Peter Hulm -- Kaori Hayashi -- Asbjørn Simonnes and Gudmund Gjeltsen -- Philip M. Taylor -- Bernhard Debatin -- Robert S. Fortner -- Haydar Badawi Sadig, Roshan Noorzai, and Hala Asmina Guta -- P. Mark Fackler -- Robert S. Fortner. Jane B. Singer -- Jiafei Yin -- Oliver Witte -- Jarice Hansen -- Vijay Mishra -- Boniface Omachonu Omatta -- Paul Soukup -- Haydar Badawi Sadig and Hala Asmina Guta -- Amy Richards and Jolyon Mitchell -- Rasha A. Abdulla and Mervat Abou Oaf -- P. Mark Fickler ... [et a.] -- Zenebe Beyene -- Victor Akhterov --
Electronic reproduction.
Keywords: Communication -- Moral and ethical aspects; Mass media -- Moral and ethical aspects; Electronic books